Relevance of Mills infection periods to apple scab (Venturia inaequalis) prediction and rescheduling fungicide’ applications in Himachal Pradesh - THAKUR, V S; KHOSLA, K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1990-96 on the relevance of Mills scab infection criteria for improving efficiency in the monitored apple scab control programme. The investigations on the length of leaf wetness for the majority of infection periods (light, moderate and severe) occulted, indicated 1-3 days delay for symptoms development under Himachal Pradesh conditions. The observations recorded on potted and orchard plants showed that the light infection period required at least 3 days more for the development of scab symptoms at leaf wetness between 9.0-13.4 hr and at average temperature range between 8.S-21AoC, whereas moderate and severe infection periods (>15.0 hr leaf wetness) required 1 more day to exhibit the symptoms. The rescheduling of fungicide applications on the occurrence of infection periods, however, saved aileast 3 sprays in comparison to 8 protective sprays in the growing season. Prediction and monitored spray programme may be devised in accordance to the prevailing weather conditions of the region.